Pengaruh Pengetahuan Kewirausahaan, Lingkungan dan E-Commerce Terhadap Minat Mahasiswa Dalam Berbisnis Online Syariah - Marimin, Agus; Romdhoni, Abdul Haris; Ramadhani, Latifah (ITB AAS INDONESIA Surakarta, 2024)
This study aims to determine the effect of entrepreneurial, environmental and e-commerce knowledge on the interest of AAS Indonesia Institute of Business Technology (ITB) students in Sharia online business. This research is a quantitative study with a population of Islamic Economics study program students at the AAS Indonesia Institute of Business Technology (ITB), samples were taken using the slovin formula and the sampling used non-probability sampling technique. Data analysis using multiple linear regression. This study explains that the t test on the entrepreneurial knowledge variable has a t count of 3,533 > 1,99495 and sig α (0,001 1,99495 and sig α (0,02